REVEALING THE CHALLENGES AND PRACTICAL WAYS IN TEACHING WRITING ONLINE - Mutiatun Nasihah; Alfiah Nur Senta (Journal of English for Academic and Specific Purposes (JEASP), 2022)
The present study aims at examining the challenges confronted by the lecturers and the practical ways in teaching writing online. A qualitative research method was applied to get a deep understanding of the objective of this study. The data were collected through interviews and documentation. In obtaining the data, three English lecturers of UIN Maulana Malik Ibrahim Malang were interviewed by using a semi-structured interview. In addition, the supporting documents related to teaching writing online, such as teaching journals, teaching documents, and students’ portfolios were also gathered to enrich the data of the present study. The findings revealed that the challenges faced by the lecturers in teaching writing online include the students’ problems in internet connections and the difficulty in maintaining the students' writing process. It was difficult for the lecturers to ensure the originality of students' works; thus, the lecturers were unable to assess the actual student’s ability in writing. However, the lecturers did some practical ways to overcome the challenges in teaching writing online. Firstly, the lecturers applied synchronous and asynchronous meetings in the process of teaching and learning by utilizing some Learning Management Systems as online learning media. Secondly, the lecturers used Turnitin to check the originality of students’ works. Finally, the lecturers applied peer feedback to improve students writing skills.